Equine Methicillin-Resistant Sequence Type 398 Staphylococcus aureus (MRSA) Harbor Mobile Genetic Elements Promoting Host Adaptation - Walther, Birgit; Klein, Katja-Sophia; Barton, Ann-Kristin; Semmler, Torsten; Huber, Charlotte; Merle, Roswitha; Tedin, Karsten; Mitrach, Franziska; Lübke-Becker, Antina; Gehlen, Heidrun (Frontiers in Microbiology, 2018)
Continuing introduction of multi-drug resistant, zoonotic pathogens such as methicillin-resistant Staphylococcus aureus (MRSA) in horse clinics challenges the biosafety of employees and animal patients. This study was aimed to determine the occurrence of mobile genetic elements facilitating survival in the early stages of invasive infection in different host species, including humans and horses, in MRSA carried by equine patients admitted to a large horse clinic. A total of 341 equine patients were investigated for carriage of MRSA by hygiene screening directly at hospital admission. MRSA were further investigated by antimicrobial susceptibility testing, whole-genome sequencing and genomic composition, including virulence factors involved in immune evasion and host adaption. From a total of 340 validated specimens from equine nostrils, 3.5% yielded positive results for MRSA. All MRSA were found to be closely related belonging to sequence type (ST) 398_t011 with up to four additional antimicrobial resistances. All MRSA harbored a specific Staphylococcal Pathogenicity Island (SaPIbov5) involved in facilitating survival in ruminant and equine plasma. Moreover, a β-hemolysin (hlb) converting ϕSa3 phage encoding the human-specific Immune Evasion Cluster (IEC) was present in 72 % of the isolates. An equid-specific leukotoxin encoded by a further temperate phage (Saeq1) was only rarely detected (22 %). Despite the absence of β-hemolysin production for all IEC-positive ST398, a prominent hemolysis zone was demonstrable on sheep blood agar. Thus, IEC might remain undetected among the ST398 lineage, since the presence of IEC is commonly associated with reduction of hemolysis in S. aureus belonging to other genetic backgrounds. Here we describe MRSA-ST398 harboring different mobile genetic elements encoding variants of immune evasion factors and toxins previously shown to contribute to S. aureus invasive diseases in specific host species or ecologic niches. We suggest these combinations contribute to the adaptation of MRSA belonging to ST398 with respect to epidemic spread across different habitats and hosts, and may therefore confer a host "generalist" phenotype.